UPS For Computer Systems Protection Electricity - Riduan Riduan; Linga Hermanto, Drs. MM (Jurnal Sistem Informasi, 2004)
Computers are a means for people to help all kinds of human activities in accordance with its use. Anyone used these facilities both individuals, corporate organizations, government installations and by those who use computers. But what if the computer's performance is affected by the lack of protection against electricity. In this case developed a device that UPS needed to overcome the problem of electricity computers. With UPS is expected to minimize all forms of electricity shortages on the computer used.